2017
DOI: 10.1016/j.ypmed.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing participation in colorectal cancer screening programs in Spain

Abstract: To analyze the sociodemographic and organizational factors influencing participation in population-based colorectal cancer screening programs (CRCSP) in Spain, a retrospective study was conducted in a cohort of people invited to participate in the first 3 screening rounds of 6 CRCSP from 2000 to 2012. Mixed logistic regression models were used to analyze the relationship between sociodemographic and organizational factors, such as the type of fecal occult blood test (FOBT) used and the FOBT delivery type. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(14 reference statements)
0
3
1
Order By: Relevance
“…While previous studies in the Spanish population found that women were more likely to participate in CRC cancer screening programmes [24,[47][48][49][50], sex was not associated with having had an FOBT in our study. Regarding country of birth, we found that nonparticipation in the screening programme was associated with being born outside of Spain, which is in line with the findings reported by Rosano et al in 2017 [51].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…While previous studies in the Spanish population found that women were more likely to participate in CRC cancer screening programmes [24,[47][48][49][50], sex was not associated with having had an FOBT in our study. Regarding country of birth, we found that nonparticipation in the screening programme was associated with being born outside of Spain, which is in line with the findings reported by Rosano et al in 2017 [51].…”
Section: Discussioncontrasting
confidence: 88%
“…The strategies implemented in the autonomous communities with higher coverage include those aimed at improving healthcare access among vulnerable people, identifying the barriers to and facilitators of participation in screening, and reducing inequalities in participation. The associated activities include holding meetings with political leaders of the autonomous communities; sending information to be distributed throughout the municipalities in collaboration with city councils; sending tests to homes and enabling participants to submit samples in all primary care centres; sending tests to care homes; conducting cross-sectional analyses of participants and non-participants to identify their profiles and thus develop specific strategies to increase uptake; increasing participation through informative talks in the press and on the radio; implementing the practice of reminder calls from medical and/or nursing staff; holding talks in collaboration with the Spanish Association Against Cancer (AECC); and ensuring that in all primary care centres, people eligible for screening are educated about its importance before being invited for the test [24,47,49,55,64]. In the autonomous communities with lower participation, these activities are only partially implemented, if at all.…”
Section: Discussionmentioning
confidence: 99%
“…The CRIBEA-CIN project is a multicentric retrospective cohort study of participants in CRCSPs carried out in the Valencian Community, Region of Murcia, Canary Islands, and the Basque Country (all located in Spain). The characteristics of these programs can be seen in the study of Vanaclocha-Espi et al, 2017 [23]. This project was born with the aim of studying the balance between predictive indicators of the benefits and adverse effects of CRCSPs.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all studies show a large increase in participation when including the FIT sample kit with the invitation. 8,[11][12][13] One Italian study showed only a modest increase in participation, but this study was performed in previously screened individuals (used to another screening strategy). 14 One French study showed low uptake rates when directly mailing the FOBT.…”
Section: Discussionmentioning
confidence: 99%